مدى احتواء مقرر "العلوم والبيئة" للصف الثاني عشر لمعايير التربية البيئية المعتمدة من قبل رابطة أمريكا الشمالية (NAAEE): دراسة من وجهة نظر المعلمين - Ali Al-Hammdi, F.A.; Abd. Rahman, L. (Universiti Sains Islam Malaysia, 2024)
This quantitative study aimed to determine the extent of Science and Environment course for the 12th grader in the Sultanate of Oman included the environmental education standards adopted by the North American Association (NAAEE). Due to the six basic criteria adopted by the Association in their educational decisions, which include: Describe environmental problems, raise awareness to the age level of students, provide skills to avoid environmental problems, work towards civil responsibility towards environmental issues and problems, effective teaching in an effective learning environment, and design ability. The study adopted descriptive analytical approach. The data were collected from the sample of (22) teachers from the study population (36) in Muscat educational area, using a questionnaire from the researcher's design, consisting of (41) paragraphs covering the six criteria. The data were analyzed using standard averages and standard deviations. The findings revealed that: The criteria reached the highest of the six, with an average of 3.55. The terms indicated that there was little variation in the interest in linking the topics of the course to the experiences of the learners and to support their participation in solving the issues of the community. The usability criterion was less included, with an average of (2.05).